If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -15 = 6x + 8 Reorder the terms: -15 + 7x = 6x + 8 Reorder the terms: -15 + 7x = 8 + 6x Solving -15 + 7x = 8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -15 + 7x + -6x = 8 + 6x + -6x Combine like terms: 7x + -6x = 1x -15 + 1x = 8 + 6x + -6x Combine like terms: 6x + -6x = 0 -15 + 1x = 8 + 0 -15 + 1x = 8 Add '15' to each side of the equation. -15 + 15 + 1x = 8 + 15 Combine like terms: -15 + 15 = 0 0 + 1x = 8 + 15 1x = 8 + 15 Combine like terms: 8 + 15 = 23 1x = 23 Divide each side by '1'. x = 23 Simplifying x = 23
| 7=2b-3 | | 4x+11=41 | | 0.06x+0.09(15-x)=0.07 | | 3x-4=9-2x | | 2x=-4x-6 | | 6(2-7r)=-27 | | 15-3s=3 | | 91=4u+15 | | 13x=145 | | 9b-10-8b=-13 | | 16-7s=-9s-20 | | 2x(4x+1)=7 | | 10x-3+3x+5=186 | | 27-9h=-4(5h-2) | | 11x=-9 | | 16-7s=9s-20 | | f(x)=x-4/x(x-4) | | 8=8(w-5)+4w | | 2/5x-16=-6 | | 0.675*t^2-2*t+2=0 | | 2(2k+1)x+5(2k+1)y-3k-1=0 | | 1/3(2x-3)3/4(2-4x) | | 20=3(y+4)-7y | | 6x+4=7x-19 | | 1+4u-16=3u-5 | | 2/5x-16= | | 3(v-2)-5v=2 | | x^2-8x^2=9 | | 6(9k-7)=-30 | | 0.675*t^2-2*t=-2 | | 4-(x-5x)=8-2x | | 3a-4=k |